Genetic diversity of Leptospira interrogans circulating isolates and vaccine strains in China from 1954–2014 - Cuicai Zhang; Zhe Li; Yinghua Xu; Ying Zhang; Shijun Li; Jinlong Zhang; Shenghui Cui; Zongli Du; Xiaofang Xin; Yung-Fu Chang; Xiugao Jiang; Qiang Ye (Human Vaccines & Immunotherapeutics, 2019)
Leptospirosis is one of the most important but neglected, infectious tropical diseases worldwide. Leptospira interrogans is now recognized as a leading cause of the disease. Little is known of the genetic diversity and phylogenetic characteristics of L. interrogans within China. To better understand the transmission and genetic diversity of L. interrogans populations, we characterized 271 isolates and seven vaccine strains from China during 1954–2014 using multilocus variable-number tandem repeat analysis (MLVA). 110 different L. interrogans MLVA profiles (MTs) were identified, of which five were predominant, reflecting a high level of genetic diversity in L. interrogans population in China. Different from that of circulating isolates, seven vaccine strains have different MT, of which some are phylogenetically away from the circulating isolates. The results showed that Icterohaemorrhagiae, Hebdomadis, and Canicola ranked as the top three serogroups among L. interrogans strains tested. The cluster analysis demonstrate the clonal links between rodent and human isolates, suggesting the rodent species played a key role in the transmission of leptospirosis to humans, and contributed to the circulation of the pathogen in humans. Taken together, these findings should provide insight into a better knowledge of the epidemiology and molecular evolution of L. interrogans in China. Furthermore, the results should facilitate the selection of candidate vaccine strains in the future.